Feeding preferences of Spodoptera frugiperda in response to new different artificial diet formulas - Megasari, Dita; Atasa, Dita; Damayanti, Denia Rista; Maulana, Arman Adrian; Najiyah, Aliyatul; Khoiri, Syaiful (Agrovigor, 2025)
Maize is an important food commodity that is vulnerable to pest attacks, one of which is the fall armyworm (Spodoptera frugiperda). This invasive pest targets the growing points of maize plants, leading to decreased productivity. To support biological research on this pest, the development of artificial diets is crucial due to the limitations of natural feed. This study aimed to evaluate the effect of artificial diet formulations on the feeding preference of S. frugiperda larvae. Three diet formulations with varying compositions were tested. Preference tests were conducted on third-instar larvae to observe their quick response and measure feed consumption (daily intake). Preference tests were performed over time intervals of 1, 2, 4, 6, and 24 hours. The attraction results showed that formula 3, which included natural ingredients such as baby corn and maize sprouts, had the highest initial attraction (30% within 1 hour). The physical and chemical characteristics of the artificial diets influenced the larvae's preference, with formula 3 being more effective for quick response, while formulas 1 and 2 were more stable for prolonged use. The highest daily consumption by larvae was observed with formula 3 (0.066 ± 0.027 grams), although it was not significantly different from formula 1 (0.058 ± 0.029 grams). However, formula 3 was considered the most optimal for maximising feed consumption. Bite marks and feeding holes indicated that the larvae consumed and damaged the feed during the maintenance process.